Aging and the governance of the healthcare system in Japan - Yukihiro Matsuyama (Bruegel, 2014)
Japan is the most rapidly aging country in the world. This is evidence that the social security system, which consists of the pension system, healthcare system and other programmes, has been working well. The population is shrinking because of a falling birth rate. It is expected that the population will fall from 128 million in 2010 to 87 million in 2060. During this period, the ratio of people aged 65 or over will rise from 23 percent to 39.9 percent. Japan's age dependency ratio was 62 in 2013, the highest among advanced nations. It is expected to rise sharply to 94 in 2050 (see Figure 1 on page 4). A total reform of the Japanese social security system, therefore, is inevitable. From the point of view of fiscal reconstruction, reform of the healthcare system is the most important issue. The biggest problem in the healthcare system is that both the funding system and the care-delivery system are extremely fragmented. The government is planning its reform of the healthcare system based on the principle of integration. Other advanced economies could learn from the Japanese experience.
Keywords: 330